Prognostic Significance of Hyponatremia Leukocytosis, Hypomagnesemia, and Fever after Aneurysmal Subarachnoid Hemorrhage - Vladimir, Vrsajkov; Gordana, Jovanović; Marija, Galešev; Arsen, Uvelin; Dunja, Glišić; Jelena, Pantić-Vrsajkov (Indian Journal of Neurosurgery, 2015)
Background Early identification of patients at an increased risk for delayed cerebral ischemia (DCI) and poor outcome could allow more aggressive therapy and influence better outcome. The aim of this study was to determine a predictive association of hyponatremia, hypomagnesemia, fever, and leukocytosis with DCI and poor outcome.Patients and Methods We prospective enrolled 68 patients with subarachnoid hemorrhage (SAH) treated from March 2011 to May 2013. Serum levels of sodium, magnesium, and leukocyte count were determined at least once a day during the first 10 days after SAH. All patients underwent noncontrast computed tomography (CT) scan 9 ± 2 days after SAH. DCI was defined as one or more of the next parameters: a new focal neurological deficit, decline for two or more points on the modified Glasgow Coma Scale or a new hypodensity on CT scan. The outcome was assessed after 6 months using the extended Glasgow Outcome scale.Results Overall, 48% of the patients recruited had DCI. Ramachandraiah logistic regression model showed significant impact of hyponatremia (p = 0.036; odds ratio [OR] = 4.08; 95% confidence interval [CI] = 1.09–15.26) on DCI and poor outcome (p = 0.034; OR = 5.11; 95% CI = 1.13–23.14). We obtained strong correlation of leukocytosis (p = 0.013) with DCI and poor outcome (p = 0.016). Association of noninfectious fever and hypomagnesemia with DCI existed, but it was not significant enough.Conclusion Our results confirmed the association of hyponatremia and leukocytosis with greater risk of developing DCI and poor clinical outcome.
Keywords: subarachnoid hemorrhage; cerebral ischemia; Glasgow outcome scale; Hyponatremia; magnesium